Answer:
-x^3+5x^2-8x+1, which is choice A
======================================
Work Shown:
f(x) = x^3 - x^2 - 3
f(x) = (x)^3 - (x)^2 - 3
f(2-x) = (2-x)^3 - (2-x)^2 - 3 ................ see note 1 (below)
f(2-x) = (2-x)(2-x)^2 - (2-x)^2 - 3 ........... see note 2
f(2-x) = (2-x)(4-4x+x^2) - (4-4x+x^2) - 3 ..... see note 3
f(2-x) = -x^3+6x^2-12x+8 - (4-4x+x^2) - 3 ..... see note 4
f(2-x) = -x^3+6x^2-12x+8 - 4+4x-x^2 - 3 ....... see note 5
f(2-x) = -x^3+5x^2-8x+1
----------
note1: I replaced every copy of x with 2-x. Be careful to use parenthesis so that you go from x^3 to (2-x)^3, same for the x^2 term as well.
note2: The (2-x)^3 is like y^3 with y = 2-x. We can break up y^3 into y*y^2, so that means (2-x)^3 = (2-x)(2-x)^2
note3: (2-x)^2 expands out into 4-4x+x^2 as shown in figure 1 (attached image below). I used the box method for this and for note 4 as well. Each inner box or cell is the result of multiplying the outside terms. Example: in row1, column1 we have 2 times 2 = 4. You could use the FOIL rule or distribution property, but the box method is ideal so you don't lose track of terms.
note4: (2-x)(4-4x+x^2) turns into -x^3+6x^2-12x+8 when expanding everything out. See figure 2 (attached image below). Same story as note 3, but it's a bit more complicated.
note5: distribute the negative through to ALL the terms inside the parenthesis of (4-4x+x^2) to end up with -4+4x-x^2
Answer: 69
Step-by-step explanation: a triangle adds up to 180 degrees. It is an isosceles triangle (2 sides are the same angle) 180-42=138 then do 138/2=69
Using the diagonal dimension and the height we can solve for the diameter of the cylinder using the Pythagorean theorem.
x^2 + 9.5^2 = 19.3^2
x^2 + 90.25 = 372.49
x^2 = 372.49 - 90.25
x^2 = 282.24
x = √282.24
x = 16.8
Now we know the diamteer and height, we can calculate the volume using the formula V = pi * r^2 * h
r = 1/2 the diameter = 16.8/2 = 8.4
using 3.14 for pi
Volume = 3.14 * 8.4^2 * 9.5
V = 3.14 * 70.56 * 9.5
v = 3.14 * 670.32
v = 2104.8 cubic meters
Write out the equation;
y=a^b
y=(-2)^2
y=(-2)(-2)
y=4
Therefore, the value of a^b is 4
Hope I helped :)
The answer is the 3rd one: 7n-2p